1991
DOI: 10.1161/01.res.68.2.402
|View full text |Cite
|
Sign up to set email alerts
|

Cellular versus myocardial basis for the contractile dysfunction of hypertrophied myocardium.

Abstract: Contractile dysfunction has been demonstrated in many previous studies of experimental right ventricular pressure-overload hypertrophy; however, given the complex changes that occur both in the cardiac muscle cell and in the multiple components of the cardiac interstitium, it is not clear whether the contractile dysfunction observed is an intrinsic property of the cardiac muscle cell or whether it is the result of a mechanically normal cardiac muscle cell contracting within an abnormal interstitial environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 50 publications
4
36
0
1
Order By: Relevance
“…In many patients, right ventricular DCM was coupled with the occurrence of a dilated right atrium [3]. At the structural level, DCM was associated with a loss of myofibrils and sarcomeric disorganization [4,5]. The inherited forms of DCM are associated with mutations in genes that generally encode cytoskeletal and sarcomeric proteins [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…In many patients, right ventricular DCM was coupled with the occurrence of a dilated right atrium [3]. At the structural level, DCM was associated with a loss of myofibrils and sarcomeric disorganization [4,5]. The inherited forms of DCM are associated with mutations in genes that generally encode cytoskeletal and sarcomeric proteins [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…These cardiac sarcomeric defects are similar to those observed in mice heterozygous for the ␣-myosin heavy chain knockout (24) with numerous degenerating fibers. Loss of myofibrils is the most obvious structural change in many cardiomyopathies (25) and sarcomeric disarray is characteristic of failing hearts (26). Several studies have suggested a role for Gq-coupled receptors in various heart compartments (27) and Gq has been shown to regulate cardiomyopathy development.…”
Section: Resultsmentioning
confidence: 99%
“…The hearts were then enzymatically digested using techniques standard in this laboratory (24,30). After enzymatic digestion of the heart, the cells were rinsed with KHB and gently centrifuged (200 g) to separate the myocyte from nonmyocyte cell types.…”
Section: Cellular Source For Myocardial Tnfa Production In Vitromentioning
confidence: 99%